Why do Camera Lenses Appear Coloured? - Sharma, B.K. (SCHOOL SCIENCE, 2013)
The optical components, such as lenses, prisms and mirrors of a large variety of optical instruments (e.g. still/movie or TV cameras, binoculars, telescopes, microscopes, etc.) make use of the laws of reflection and refraction of light. The purpose of each of such instrument is to form as true an image as possible of the object. When a beam of light is incident on the boundary or interface between two media of different refractive indices (e.g. a glass plate/lens or a prism placed in air/liquid), a part of the light energy is transmitted, a part is absorbed and the remaining part is reflected from the surface. The transmitted or reflected light may form an image of the object if the light rays actually meet after transmission or reflection. The resulting image is often not distinct, on account of the stray light accompanying the transmitted or reflected light due to surface reflections. The quality of a camera basically depends on ability of its lens system to transmit light through the glass. This ability depends on the surface area of the lens facing the object. In case of high quality movie or TV cameras, the optical system consists of multi-element lens system (a combination of several lenses), the light due to reflection from each of the refracting surfaces, reduces greatly the net transmission of light energy through it. In addition to lower transmission of light energy, the lens suffers from another drawback due to the surface reflections. The light reflected at the various surfaces may reach the focal plane of the camera in a random way here it gives rise to a ‘ghost image’, thereby reducing the contrast of the final image. In order to obtain a sharp picture/image, it is essential to reduce, by some means intensity losses due to the surface reflection of the camera lens.